IMPLEMENTATION INTERNAL QUALITY ASSURANCE IN TERMS OF ELEMENTARY SCHOOL LEARNING PROCESS - Adik Rian Saputra (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
This study aims to describe the implementation internal quality assurance in terms of elementary school learning process at SDN Semin II Gunungkidul regency. The formulation of this research is how the implementation internal quality assurance in terms of elementary school learning process. To obtain the data used qualitative research. The validity of the data is done by means of source triangulation. The analyzing the results of interviews based on the theory used and relevant research studies as a comparison material. Data analysis technique used is interactive analysis. The results can be concluded that SDN Semin II Gunungkidul regency has apply the steps of internal quality assurance in terms of elementary school learning process.